(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدف الدراسة التعرف إلى الضغوط النفسية التي تواجه المراهقين المصابين بالنوع الأول من السكري وعلاقتها ببعض المتغيرات. أجريت الدراسة على عينة مقصودة من الفئة العمرية (16-18) سنة، حيث كانت عينة المصابين بمرض السكري من النوع الأول (50) مراهقاً مصاباً (25 ذكور، 25إناث) استخدمت استبانه الضغوط النفسية التي تكونت من (30) فقرة، صيغت على شكل حدث أو موقف يتعرض له المراهق ويسبب له ضغطاً نفسياً (من إعداد الباحثة)، وقد تم استخراج دلالات الصدق (صدق المحتوى) بعرضها على عدد من المحكمين، كما تم التأكد من ثبات الاستبيان بطريقة التجزئة النصفية حيث بلغ معامل ثبات بطريقة سبيرمان _ براون (0.82) ومعامل جوتمان (0.82). وهذه النتائج تدل على أن المقياس يتمتع بثباتٍ عالٍ يجعله صالحاً للاستخدام. وقد أظهرت النتائج أن المراهقين المصابون بالسكري النمط الأول يتعرضون لضغوط مرتفعة، كما وجد علاقة بين الضغوط النفسية ودخول المشفى، حيث كلما زاد عدد مرات دخول المشفى زادت الضغوط النفسية، وأن الإناث يتعرضن لضغوط نفسية أكثر من الذكور، ولم يظهر التحليل الإحصائي علاقة دالة إحصائياً بين الضغوط النفسية والعمر عند التشخيص. The study aims to identify the psychological pressures faced by adolescents with type (A) diabetes and its relationship to some variables. The study was intentionally conducted on an age group (16-18) years, where the sample consisted of (50) teenagers with diabetes type (A) (25 males, 25 females). A questionnaire of (30) items on psychological pressures was used to. It was designed on the form of an event which the teenager faces and suffers from a psychological pressure (prepared by the researcher). Indications of true content were extracted by showing it to a number of arbitrators. The stability of the questionnaire was proved by way of retail midterm where the Spearman reliability coefficient-Brown reached (0.82) and Guttman coefficient reached (0.82). These results indicate that the measure is consistently high, which makes it fit for use. The results showed that adolescents with diabetes type(A) are under high stress. Moreover, the existence of a relationship between the psychological pressures and entering the hospital. The more the times of entering the hospital, the higher the psychological pressure is. The females are subjected to psychological pressures more than males, but the statistical analysis did not show statistically significant relationship between pressure sand age at diagnosis.